Transparency of COVID-19-Related Research in Dental Journals - Sofi-Mahmudi, Ahmad; Raittio, Eero (Frontiers in Oral Health, 2022)
Objective: We aimed to assess the adherence to transparency practices (data availability, code availability, statements of protocol registration and conflicts of interest and funding disclosures) and FAIRness (Findable, Accessible, Interoperable, and Reusable) of shared data from open access COVID-19-related articles published in dental journals available from the Europe PubMed Central (PMC) database. Methods: We searched and exported all COVID-19-related open-access articles from PubMed-indexed dental journals available in the Europe PMC database in 2020 and 2021. We detected transparency indicators with a validated and automated tool developed to extract the indicators from the downloaded articles. Basic journal- and article-related information was retrieved from the PMC database. Then, from those which had shared data, we assessed their accordance with FAIR data principles using the F-UJI online tool (f-uji.net). Results: Of 650 available articles published in 59 dental journals, 74% provided conflicts of interest disclosure and 40% funding disclosure and 4% were preregistered. One study shared raw data (0.15%) and no study shared code. Transparent practices were more common in articles published in journals with higher impact factors, and in 2020 than in 2021. Adherence to the FAIR principles in the only paper that shared data was moderate. Conclusion: While the majority of the papers had a COI disclosure, the prevalence of the other transparency practices was far from the acceptable level. A much stronger commitment to open science practices, particularly to preregistration, data and code sharing, is needed from all stakeholders.